In vitro Evaluation of Different Feeds for Their Potential to Generate Methane and Change Methanogen Diversity - Kim, Seon-Ho (Asian-Australasian journal of animal sciences, 2013)
Optimization of the dietary formulation is the most effective way to reduce methane. Nineteen feed ingredients (brans, vegetable proteins, and grains) were evaluated for their potential to generate methane and change methanogen diversity using an in vitro ruminal fermentation technique. Feed formulations categorized into high, medium and low production based on methane production of each ingredient were then subjected to in vitro fermentation to determine the real methane production and their effects on digestibility. Methanogen diversity among low, medium and high-methane producing groups was analyzed by PCR-DGGE. The highest methane production was observed in Korean wheat bran, soybean and perilla meals, and wheat and maize of brans, vegetable protein and cereal groups, respectively. On the other hand, corn bran, cotton seed meal and barley led to the lowest production in the same groups. Nine bacteria and 18 methanogen 16s rDNA PCR-DGGE dominant bands were identified with 83% to 99% and 92% to 100% similarity, respectively. Overall, the results of this study showed that methane emissions from ruminants can be mitigated through proper selection of feed ingredients to be used in the formulation of diets